Body mass index and distribution of body fat can influence sensory detection and pain sensitivity. (6th March 2017) - Tashani, O. A; Astita, R.; Sharp, D.; Johnson, M. I
Abstract: Background: The aim of this study was to investigate the influence of body fat percentage and its distribution on sensory detection and pain sensitivity responses to experimentally induced noxious stimuli in otherwise pain‐free individuals. Methods: Seventy‐two participants were divided into three equal groups according to their body mass index (BMI: normal, overweight and obese). Percentage body fat was estimated using a four‐site skinfold method. Measurements of cold pressor pain threshold, tolerance and intensity; contact thermal sensory detection and heat pain threshold and tolerance (TSA‐II – NeuroSensory Analyzer, Medoc); and blunt pressure pain threshold (algometer, Somedic SenseLab AB) were taken at the waist and thenar eminence. Results: Mean ± SD pressure pain threshold of the obese group (620.72 ± 423.81 kPa) was significantly lower than normal (1154.70 ± 847.18 kPa) and overweight (1285.14 ± 998.89 kPa) groups. Repeated measures ANOVA found significant effects for site for cold detection threshold ( F 1, 68  = 8.3, p  = 0.005) and warm detection threshold ( F 1, 68  = 38.69, p  = 0.001) with waist having lower sensory detection thresholds than thenar eminence. For heat pain threshold, there were significant effects for site ( F 1, 68  = 4.868, p  = 0.031) which was lower for waist compared with thenar eminence (mean difference = 0.89 °C). Conclusion: Obese individuals were more sensitive than non‐obese individuals to pressure pain but not to thermal pain. Body sites may vary in their response to different types and intensities of stimuli. The inconsistency of findings within and between research studies should catalyse further research in this field. Significance: This study provided evidence that body mass index and distribution of body fat can influence sensory detection and pain sensitivity. Obese individuals were more sensitive than normal range body mass index individuals to pressure pain but not to thermal pain. Pain response varied according to subcutaneous body fat at different body sites. These findings strengthen arguments that weight loss should be a significant aspect of a pain management programme for obese pain patients.